In silico discovery of α-glucosidase inhibitors from Mitragyna speciosa for antidiabetic therapy - Mat Rasid, Siti Norain; Khatib, Alfi; Nando, Dendi Noventri; Ahmad Mizher, Hussam Abdeljabar; Mohd Nasir, Mohd Hamzah; Arzmi, Mohd Hafiz (National Institutes of Health (NIH), 2025)
INTRODUCTION: Mitragyna speciosa (kratom) is a medicinal plant known for its richness in phytochemicals with potential antidiabetic activity. α-glucosidase is an enzyme that plays a key role in carbohydrate hydrolysis. The inhibition of α-glucosidase activity represents a validated therapeutic approach to manage postprandial hyperglycaemia in type 2 diabetes. This study investigates the potential of M. speciosa leaf extract as an α-glucosidase inhibitor.